THE ANALYSIS ON THE STRUCTURE OF TRADITIONAL DANCE MAENGKET - Zefanya Christofel Sumarandak; Luccylle M. Takalumang; Franklin Dumasi (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research aims to explore the musical structure of Maengket Art, a performing arts tradition in Kaweng village, Kakas sub-district, Minahasa district. Maengket art is typically performed in harvest ceremonies as a form of expression of gratitude and joy towards God for the harvest obtained by the local community. Maengket art performances generally involve many dancers and involve both male and female dancers dancing in pairs. Maengket art is divided into three main parts, namely Maowey Kamberu, Marambak, and Lalayaan. The choice of the title of this research was based on the researcher's interest in the musical structure of Maengket Art songs, especially those that take place in Kaweng village, Kakas sub-district. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The validity of the data is checked carefully, then the data is analyzed through reduction, presentation and verification processes. The results of the research show that in Kaweng village, Kakas subdistrict, Minahasa district, there is a Maengket Art group which has been established since 1968. This Maengket Art adopts Toulour literature as an integral part of their performances. Chapters of Maengket Art in Kaweng village, such as Maowey Kamberu, Marambak, and Lalayaan, depict various aspects of local community life. Maowey Kamberu expressed his gratitude for the abundant harvest, Marambak highlighted the spirit of mutual cooperation in the housewarming ceremony, while Lalayaan described the interactions between Minahasan youth in looking for a soul mate or social relationships in the past.